Sexual transactions as a means of acquiring drugs among inmates in Papua, Indonesia - Fatiah, Mona Safitri; Tambing, Yane; Irjayanti, Apriyana; Bela, Sarni Rante Allo; Irmanto, Maxsi; Mollet, Genoveva C C; Sirait, Evelyn Gyan (Jurnal Cakrawala Promkes, 2025)
Transactional sex has been recognized as a significant element hindering the reduction of drug usage in Papua, Indonesia. The national objective for drug usage reduction was established at 1.67% for 2024; nevertheless, this target remains unfulfilled. This research investigated the correlation between transactional sex and substance abuse among female and adolescent prisoners in Papua Province. A case-control approach was utilized, employing primary data gathered from May to September 2023 at the Special Correctional Institution for Juveniles (LPKA) and the Women’s Correctional Institution (LPP) in Papua. The research population consisted of 85 offenders incarcerated from 2021 to 2023. A total of 26 cases (drug users) and 59 controls (non-users) were included using total sampling, in a 1:2 ratio. Data were gathered using a modified version of the Rapid Survey Questionnaire on Injecting Drug User Behavior (SCP Penasun). Analysis was conducted using STATA version 14, employing multivariate logistic regression to identify related factors. In all, 30.6% of participants were identified as drug users according to case-control selection, rather than as an estimation of population-level prevalence. Inmates who indicated participation in transactional sex exhibited increased odds of drug acquisition (adjusted OR: 1.59; 95% CI: 0.46–5.39) after controlling for work status, past-year drug usage, and duration of use. The findings suggest a possible trend of heightened drug acquisition among inmates engaged in transactional sex, although the correlation remains ambiguous. Consequently, integrated therapies targeting both substance use and sexual risk behaviors are crucial in custodial environments.